Alzheimer's Disease: From Genes to Nutrition. (September 2014) - Venturini, L.; Perna, S.; Sardi, F.; Faliva, M.A.; Cavagna, P.; Bernardinelli, L.; Ricevuti, G.; Rondanelli, M.
Alzheimer's disease (AD) is widely identified as the most common cause of sporadic dementia. Its aetiology is still debated, as despite several hypotheses, different factors seem to play a role in its establishment and development. Recent studies have proposed a possible preventing role of nutrition. The weight loss typical of earlier phase of disease and the finding of malnutrition as a common trait between patients leads to hypothesize that a supplementation of specific nutrients seems to be useful and effective in terms of improvement of cognitive functions. Malnourished patients show also altered parameters when investigating inflammation markers: for example, hyperhomocysteinemia is a typical finding in elderly affected by dementia, and it can be prevented and corrected by using a proper nutrients supplementation. Pro-inflammatory state can be reduced with supplementation of polyunsaturated fatty acids, vitamins of the group B and phosphatidylserine, that can act reducing IL-1β (pro-inflammatory cytokine) and improving IL-10 (anti-inflammatory cytokine) synthesis. While investigating the role of nutrition, it seems to be deeply linked with genetic; a genetic onset AD-related could be latent and can be influenced by nutritional attitude. AD can be considered a sort of latent clinical condition that would disclose or not, depending also on micro-environment and nutritional parameters. The genetic expression can be influenced by assumptions or not of specific nutrients, with the promotion of different pro- or anti-inflammatory settings. The specific role of each micronutrient (in particular vitamins) and trace elements still needs to be punctuated, as they are involved in a pool of different reactions. Also genes acts not independently but in an interconnected pattern, in which the role of a single gene needs to be cleared, depending on others. This complex system of predisposing conditions and a possible role of nutrition as modulator of the inflammatory state is the object of this review.